ANALYSIS OF STUDENT LEARNING ACTIVITY IN THE FIRST MIDDLE SCHOOL OF JAMBI CITY - Nur Ika Sandi Pratiwi; Astalini Astalini; Dwi Agus Kurniawan (JURNAL SPEKTRA, 2021)
The purpose of this study was to determine the activeness of student learning in science subjects at Junior high school 18 Jambi City, Junior high school 21 Jambi City, and Junior high school 24 Jambi City. The research method used is a mixed research method with an explanatory design. The research subjects were students of Junior high school 18 Jambi City, students of Junior high school 21 Jambi City, and students of Junior high school 24 Jambi City, totaling 567 students. The data analysis technique used descriptive statistics for quantitative data and Miles Huberman's analysis for qualitative data. The results of the study on the three indicators show that students are categorized as having good learning activeness on the indicator " Physical Activeness (59.3%) " Intellectual activity (45.5%) "Emotional Activeness (46.7%) "and for the indicator," Mental Activeness (43.7%) "is in the sufficient category. The high percentage of the four indicators is supported by the results of interviews which state that students have good physical activity, seen from students who are active in conducting experiments, students do not only see but also participate in carrying out the exercise according to the experimental process. Then intellectual activeness can be seen from students who actively ask questions and also don't just rely on the material provided by the teacher. Furthermore, the indicators of mental activeness are in the quite visible category of students who have begun to dare to express their opinions or work on questions in front of the class. And the indicators of emotional activeness are in a good category, seen from students who are stinging and enthusiastic in implementing science learning.